Synthesis and herbicidal activity of N-(2-pyridyloxiran-2-ylmethyl) benzenesulfonamide derivatives - Hosokawa, A. (Mitsubishi Chemical Co. Ltd., Yokohama (Japan)); Katsurada, M; Mikami, E; Ikeda, O; Minami, N; Jikihara, T (Journal of Pesticide Science, 2001)
In the course of studies on sulfonamides with aryl substitutedoxirane moiety, we found that compounds having a pyridyl group on 2-position of the oxiran-2-ylmethyl moiety possessed herbicidal activity. As a result of elaborate study, 4-chloro-N-[2-(6-chloropyridin-2-yl)oxiran-2-ylmethyl]-3, N-dimethylbenzenesulfonamide and N-[2-(6-chloropyridin-2-yl) oxiran-2-ylmethyl]-N-methyl-5, 6, 7, 8-tetrahydronaphthalene-2-sulfonamide were discovered as potential rice herbicides. The former compound showed complete control of Echinochloa oryzicola (barnyardgrass) up to 2 leaf stage and broad herbicidal spectrum. The latter compound showed remarkable selectivity between rice and Echinochloa oryzicola.